2019
DOI: 10.1155/2019/7106092
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptomic Analysis Reveals Diverse Regulatory Networks That Respond to Cold Stress in Strawberry (Fragaria×ananassa)

Abstract: Strawberry is often subjected to cold stress in temperate regions when insulation measures are not strictly applied in protected cultivation. Cold stress adversely influences plant growth and development by triggering a massive change to the transcriptome. To provide the potential strategies in improving strawberry cold tolerance and give a glimpse into the understanding of the complex cold signaling pathways in plants, this study identified attractive candidate genes and revealed diverse regulatory networks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 81 publications
3
22
0
Order By: Relevance
“…The ubiquitin-mediated proteolysis pathway is involved in the immune response in Arabidopsis [76], and the carotenoid biosynthesis pathway plays important roles in fruit development, petal coloration and photosynthesis [77][78][79]. The alpha-linolenic acid metabolism pathway relates to salt tolerance and cold stress [80,81], and the phagosome pathway is involved in environmental stress [82]. These results suggested that most of the variation loci obtained from environmental correlation analysis are indeed closely related to the adaptation of species.…”
Section: Signatures Of Natural Selectionmentioning
confidence: 90%
“…The ubiquitin-mediated proteolysis pathway is involved in the immune response in Arabidopsis [76], and the carotenoid biosynthesis pathway plays important roles in fruit development, petal coloration and photosynthesis [77][78][79]. The alpha-linolenic acid metabolism pathway relates to salt tolerance and cold stress [80,81], and the phagosome pathway is involved in environmental stress [82]. These results suggested that most of the variation loci obtained from environmental correlation analysis are indeed closely related to the adaptation of species.…”
Section: Signatures Of Natural Selectionmentioning
confidence: 90%
“…Many genes indeed displayed altered expression levels in several hormone-mediated branches, such as ABA, IAA, CK, GA, ET, BR, JA, and SA. Obviously, most of the genes in auxin signaling pathway in C. maxima leaves exposed to cold stress were inhibited, which generally are obligated to cell elongation, division, cycle, and growth [13,73]. Auxin is an endogenous small molecule with an incredibly large impact on plant growth and and response to stress in concert with other hormonal pathways [74][75][76].…”
Section: Plant Hormone Signaling Involved In Cold Stressmentioning
confidence: 99%
“…Phenylalanine and tyrosine have different functions in stress resistance and are central to plant metabolism [88]. The increase in amino acids in A. thaliana, tomato, and other plants under during stress acclimation indicate that the accumulation of amino acids is related to the degradation of proteins [13,89,90]. It has been reported that the exogenous application of phenylalanine can promote chilling tolerance in tomato by activating ROS-scavenging systems; an increase in the abundance of the phenylalanine is also induced by low temperature [91].…”
Section: Carboxylic Acids and Derivatives Metabolites In Response To Cold Stressmentioning
confidence: 99%
See 2 more Smart Citations